Nutritive quality of foxtail millet (Setaria italica) grass, hay and silage, and seed fatty acid profile - Peiretti, P. G.; Tassone, S. (Cuban Journal of Agricultural Science, 2016)
Foxtail millet (Setaria italica) is grown for green grass, hay and silage and is good forage for livestock. The aim of this study was to determine the nutritive quality of foxtail millet grass, hay and silage harvested in the Po valley (northern Italy) at cut or at wilted level. The forage samples used for the trial were cut at budding stage on 8 subplots of 1 m2, randomLy located in 2 x 4 m plots. Two replicates were collected for each wilting levels: at cut (299 g/kg FM) and after 24 h of wilting (487 g/kg FM). Finally, two replicates of hay samples were collected after 36 h of wilting (918 g/kg FM) on the same two subplots, in order to determine chemical composition, gross energy, in vitro true digestibility (IVTD), indigestible neutral detergent fibre (INDF) of hay and grass samples. Moreover, herbage samples for ensiling were taken at cut and after 24 h of wilting, respectively. Foxtail millet forage was ensiled in sterile 2–litre laboratory glass silos. Two replications were performed at each dry matter level, in order to determine chemical composition, gross energy, IVTD, INDF, and fermentation characteristics of silages. The variability in herbage quality characteristics after different wilting periods and the variability in silage characteristics were analyzed for their statistical significance via analysis of variance (ANOVA) to test the effect of wilting level. Herbage wilting had no effects on nutritional parameters, reflecting excellent drying conditions. The results of ensiling indicate that the fermentation of foxtail millet is characterized by the presence of some alcohols and volatile fatty acids. No significant differences were found in crude protein, fibre, gross energy, pH or fermentation characteristics, with the exception of ethanol and butyric acid. The values of IVTD and INDF were improved in wilting silage. The good results obtained in lab–scale silos, with silage characterized by restricted fermentation at high wilting level, would seem to suggest that foxtail millet has the potential for large–scale ensiling, if it is harvested at budding stage and wilted to a DM level of more than 470 g/kg FM. Moreover, because few data are available in literature, the fat content and fatty acid (FA) profile of the seeds used in the agronomic trial were also determined. The lipid content of the foxtail millet seeds was 31.9 g/kg FM, while the predominant FAs were linoleic, oleic, and palmitic acid. The contents of stearic and linolenic acids were 32 and 27 g/kg total FA, respectively. The contents of palmitoleic, arachidic, gadoleic and behenic acid were lower than 7 g/kg total F A. Key words: Setaria italica, chemical composition, fatty acid, ensilage, forage